1970
DOI: 10.1111/j.1365-3180.1970.tb00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Field Experiments to Investigate Long‐term Effects of Repeated Applications of McPa, Tri‐allate, Simazine and Linuron: Report After 6 Years

Abstract: Summary. In five long‐term field experiments begun in 1963, each of four herbicides was applied to plots either planted with the same crop each year or uncropped. The following treatments were applied annually: MCPA at 24 oz/ac to barley at the 5‐leaf stage, triallate at 24 oz/ac to barley pre‐emergence, simazine at 24 oz/ac to maize pre‐emergence, linuron at 12–24 oz/ac to carrots preand post‐emergence. The main assessments reported in this paper are crop yield and persistence of herbicide residues. In the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0
5

Year Published

1974
1974
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 11 publications
7
51
0
5
Order By: Relevance
“…The rates of dissipation in agricultural soils determined by laboratory and field experiments are highly variable, with values ranging from days to several years (2,8,9,11,16,23). Linuron is frequently detected in surface and ground waters near or below areas with intensive use, and in one extreme case, linuron was detected in a drinking-water well in concentrations up to 2,800 g liter Ϫ1 (2).…”
Section: The Phenylurea Herbicide Linuron [N-(34-dichlorophenyl)-nј-mentioning
confidence: 99%
“…The rates of dissipation in agricultural soils determined by laboratory and field experiments are highly variable, with values ranging from days to several years (2,8,9,11,16,23). Linuron is frequently detected in surface and ground waters near or below areas with intensive use, and in one extreme case, linuron was detected in a drinking-water well in concentrations up to 2,800 g liter Ϫ1 (2).…”
Section: The Phenylurea Herbicide Linuron [N-(34-dichlorophenyl)-nј-mentioning
confidence: 99%
“…A partir de então, houve sintomas ocasionais na planta-teste. Fryer & Kirkland (1970) observaram que a maior quantidade de linuron é encontrada nos primeiros 5cm do solo; portanto, a perda da atividade do produto não pode ser devida à percolação à camada mais profunda. A rápida degradação, segundo Walker (1978), também não se deve à temperatura.…”
Section: Resultsunclassified
“…(1985) e Fryer & Kirkland (1970), sob certas condições, quando repetidas aplicações de pesticidas são feitas no mesmo local, a persistência e a eficiência do produto diminuem, havendo ausência de uma lag fase mais longa no processo de degradação de alguns pesticidas de solo.…”
Section: Resultsunclassified
“…Residues of both herbicides have been found in the soil 1 yr after treatment in quantities sufficient to damage susceptible crops (Roadhouse and Birk l96l; Morris and Penney 1971;Ragab 1974;Smith and Emmond 1975). Despite this potential for persistence, no large accumulations of simazine have been found in cases where relatively high rates were applied for up to 9 yr to the same soil, although carry-over ofresidues from year to year occurred (Dawson et al 1968;Fryer and Kirkland 1970;Bowmer 1972; Leonard et al 1974). In a previous study on residue accumulation after long-term linuron application, no significant buildup was observed (Fryer and Kirkland 1970).…”
mentioning
confidence: 99%
“…Despite this potential for persistence, no large accumulations of simazine have been found in cases where relatively high rates were applied for up to 9 yr to the same soil, although carry-over ofresidues from year to year occurred (Dawson et al 1968;Fryer and Kirkland 1970;Bowmer 1972; Leonard et al 1974). In a previous study on residue accumulation after long-term linuron application, no significant buildup was observed (Fryer and Kirkland 1970). Movement of these herbicides into the soil profile was restricted essentially to the top l5 cm, with the majority of herbicide being found in the top 5 cm (Roadhouse and Birk 1961;Dawson et al 1968;Fryer and Kirkland 1970 At moderate rates simazine has generally been observed to persist longer than linuron (Kearney et al 1969;Fryer and Kirkland 1970) although Fryer and Kirkland (1970) found that when rates of these herbicides high enough to cause carry-over were applied, the residues of linuron were usually greater than those of simazine.…”
mentioning
confidence: 99%